Alua Jo Patuik With Raso Jo Pareso, How the Minangkabau to Find the Truth (Ethnographic Study of Nagari Sisawah, Sumpur Kudus District, Sijunjung Regency, West Sumatra) - Ulma Tiara, Inoki; Nofirman, Nofirman (Universitas Negeri Padang, 2023)
Seribu Gonjong Tourist Village (SARUGO) which is located in Jorong Sungai Dadok, Nagari Koto Tinggi, Gunung Omeh District, Limapuluh Kota, West Sumatra is one of 50 villages that was named the best tourist village by the Minister of Tourism and Creative Economy. This achievement cannot be separated from the role of Pokdarwis in managing natural and cultural tourism. The Minangkabau social system, which is known to uphold a sense of togetherness, has an impact in developing programs for independence and improving the community's economy through community empowerment. Empowerment is defined as an effort to fulfill the desired needs of individuals, groups and communities, in controlling their environment so that they can fulfill their desires, including accessibility to resources related to their work and developing the potential of local resources. Based on the description above, this research has the objectives of (1) To analyze the role of the Community Empowerment-based Tourism Awareness Group (POKDARWIS) in developing natural tourism potential in Seribu Gonjong Tourism Village. The method used in this research is qualitative with a case study approach. The stages of this research method are (1) Preliminary study of the research location, (2) Collecting data and profile of the SARUGO tourist village, (3) Developing instruments, (4) Data collection, (5) Analysis of findings, (6) Triangulation data, (7) drawing conclusions, and (8) preparing articles